A cultural analysis of Venda guitar songs - Kruger, Jaco Hentie (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 1994)
This thesis focuses on the articulation in music of human worldviews, and the social contexts in which they emerge. It suggests that people project various forms of social reality through symbolic systems which operate dynamically to maintain and recreate cultural patterns. The symbolic system investigated in support of this suggestion is that constituted by Venda guitar songs. In the performance of these songs, social reality emerges in a combination of symbolic forms: verbal, musical and somatic. The combination of these symbolic forms serves as a medium for individual self-awareness basic to the establishment of social reality and identity, and the drive for social power and legitimacy. A study of these symbolic forms and their performance indicates that musicians invoke the potential of communal music to increase social support for certain principles on which survival strategies in a turbulently changing society might be based. The discourse of Venda guitar songs incorporates modes of popular expression and consciousness, and thus attempts to invoke states of intensified emotion to promote these survival strategies. Performance occasions emerge as a focus for community orientation and the exploration of social networks. They promote stabilizing social and economic interaction, and serve as a basis for moral and cooperative action. Social reality also emerges in musical style, which is treated as the audible articulation of human thought and emotion. Stylistic choices are treated as integral to the conceptualization of contemporary existence. A study of these choices reveals varying degrees of cultural resistance and assimilation, ranging from musical styles which are essentially rooted in traditional social patterns, to styles which integrate traditional and adopted musical elements as articulations of changing self-perceptions, social aspirations, and quests for new social identity.
Keywords: Ethnomusicology; Venda (African people) -- Music -- Social aspects; Songs with guitar Music -- Social aspects; Music -- Social aspects -- South Africa -- Venda; Symbolism in music